Power relations in dating relationships: A phenomenological study of violence in university students in Samarinda City - Ade Juni Widyananda; Asia Ashfaq (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2023)
In 2022, cases of violence against women and children in East Kalimantan Province increased by 315 cases in just four months. Samarinda City is in first place for cases of violence against women and children in East Kalimantan Province, with 18 victims being students. This study focuses on the experiences and impacts of violence experienced by female students in Samarinda City as victims of violence in dating relationships. This type of research is qualitative research with a phenomenological approach. This study employed Michel Foucault’s power relations theory. Data acquisition was carried out through in-depth interviews. The data was then processed using the Creswell method. This study found that patriarchal culture is still extremely strong, making the perpetrators believe that as men, they must be brave and dominant in a dating relationship to be able to maintain power and control over their partners. Victims of dating violence are willing to do whatever their partner requests in the hope that it will make their partner happier and love them more. This study concludes that the impact of violence on victims can take the form of verbal violence, physical violence, or psychological disturbances, requiring victims to seek medical assistance from a psychiatrist to help deal with mental disorders and trauma.